Students’ worksheet validity based on contextual teaching and learning in junior high school - Arnilawati Arnilawati; Armiati Armiati; Edwin Musdi (Fakultas Ilmu Pendidikan UNP)
This research was derived from the low ability of students’ problem solving. One of the factors was the students didn’t understand the problem of mathematics related to real life and the development of learning media like students’ worksheet had not been optimal yet in school. One of the efforts done was by using students’ worksheet based on Contextual Teaching and Learning (CTL). The purpose of this research is to describe the characteristics of mathematical worksheet based on CTL to improve the problem solving ability of students in junior high school that fulfills the criteria of valid. This research used plomp development model. The plomp model consists of three phases, namely preliminary research, prototyping and assessment phase. Based on the development done, it could be obtained students’ worksheet based on CTL in junior high school valid.